Bamboo forestry in China: toward environmentally friendly expansion - Ruíz Pérez, M.; Fu Maoyi; Yang Xiaosheng; Belcher, B. (2001)
Bamboo, with a long tradition in China, is one of the emerging sectors in the Chinese economy. It is making an increasingly large contribution to farmers' income and playing an important role in rural industrial development. Bamboo products are also being substituted for wood products, a process that has been accelerated by a variety of policy measures. However, the bamboo expansion has come at a cost to the environment. This article discusses the bamboo sector, with particular focus on Anji County (Zhejiang), and reviews the new policies being applied in an attempt to integrate the interests of development and the environment. (YS)